High-density Lipoproteins and Apolipoprotein A-I: Potential New Players in the Prevention and Treatment of Lung Disease - Gordon, Elizabeth M.; Figueroa, Debbie M.; Barochia, Amisha V.; Yao, Xianglan; Levine, Stewart J. (Frontiers in Pharmacology, 2016)
Apolipoprotein A-I (apoA-I) and high-density lipoproteins (HDL) mediate reverse cholesterol transport out of cells. Furthermore, HDL has additional protective functions, which include anti-oxidative, anti-inflammatory, anti-apoptotic, and vasoprotective effects. In contrast, HDL can become dysfunctional with a reduction in both cholesterol efflux and anti-inflammatory properties in the setting of disease or the acute phase response. These paradigms are increasingly being recognized to be active in the pulmonary system, where apoA-I and HDL have protective effects in normal lung health, as well as in a variety of disease states, including acute lung injury, asthma, chronic obstructive pulmonary disease, lung cancer, pulmonary arterial hypertension, pulmonary fibrosis, and viral pneumonia. Similar to observations in cardiovascular disease, however, HDL may become dysfunctional and contribute to disease pathogenesis in respiratory disorders. Furthermore, synthetic apoA-I mimetic peptides have been shown to have protective effects in animal models of acute lung injury, asthma, pulmonary hypertension, and influenza pneumonia. These findings provide evidence to support the concept that apoA-I mimetic peptides might be developed into a new treatment that can either prevent or attenuate the manifestations of lung diseases, such as asthma. Thus, the lung is positioned to take a page from the cardiovascular disease playbook and utilize the protective properties of HDL and apoA-I as a novel therapeutic approach.